2007
DOI: 10.1111/j.1365-2516.2006.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

ReFacto®1 and Advate®2: a single‐dose, randomized, two‐period crossover pharmacokinetics study in subjects with haemophilia A

Abstract: ReFacto is a recombinant B-domain-deleted, monoclonal antibody-purified, solvent-detergent-treated factor VIII (BDDrFVIII) with no albumin added to the final formulation. Although ReFacto has been shown to be bioequivalent to a plasma-derived FVIII product (Hemophil-M) in a randomized, crossover pharmacokinetic (PK) study, the comparability of ReFacto with the full-length (complete sequence) recombinant FVIII (FLrFVIII, Advate) product has not been previously examined in this manner. The primary objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 15 publications
4
45
0
Order By: Relevance
“…As expected, most of the rFVIII dispensed (89.1%) was administered to severe When not controlling for any other variables, severe patients treated on-demand utilized less FVIII than those on prophylaxis (median 1442 and 4060 IU kg )1 year )1 , respectively, P < 0.0001). After separating treatment regimen cohorts by age, there were significant differences in utilization between paediatric (<13 years old), adolescent (13)(14)(15)(16)(17)(18), and adult ( ‡19) patients receiving either episodic treatment or prophylaxis (Fig. 1, all P < 0.0001).…”
Section: Overall Fviii Utilizationmentioning
confidence: 84%
See 1 more Smart Citation
“…As expected, most of the rFVIII dispensed (89.1%) was administered to severe When not controlling for any other variables, severe patients treated on-demand utilized less FVIII than those on prophylaxis (median 1442 and 4060 IU kg )1 year )1 , respectively, P < 0.0001). After separating treatment regimen cohorts by age, there were significant differences in utilization between paediatric (<13 years old), adolescent (13)(14)(15)(16)(17)(18), and adult ( ‡19) patients receiving either episodic treatment or prophylaxis (Fig. 1, all P < 0.0001).…”
Section: Overall Fviii Utilizationmentioning
confidence: 84%
“…This reformulation of BDD-rFVIII was completed well before 2006 and would not interfere with the results. Although a pharmacokinetic crossover study [18] for the second generation BDD-rFVII product (ReFacto, Pfizer) showed BDD-rFVIII to be bioequivalent to a FL-rFVIII, half-life measurements were not provided. The follow-on BDD-rFVIII product (Xyntha in US, Refacto AF in EU, Pfizer) showed a 2-h difference in half-life between BDD-rFVIII and FL-rFVIII (11 h vs. 13 h, respectively) [19] although statistical significance was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Such direct comparison studies were performed using plasma-derived factor VIII (Hemophil M) and separately using full length recombinant factor VIII (Advate ® ; Baxter Healthcare). The direct pharmacokinetic comparisons showed that the factor VIII products are bioequivalent to each other 68,71…”
Section: Are All Currently Available Recombinant Factor VIII Productsmentioning
confidence: 99%
“…Di Paola et al conducted a clinical study using BDD-rFVIII, rAFH-PMF, and pdFVIII to compare pharmacokinetic profiles using a chromogenic substrate assay for the measurement of FVIII:C. The results indicated that BDD-rFVIII and rAFH-PMF were equivalent [22].…”
Section: Efficacy and Safety In Postmarketing Clinical Studiesmentioning
confidence: 99%